Telemedicine in Heart Failure management - Beatriz Fernandes Cruz Martins Mena (2022)
Introduction and Objectives: Heart Failure (HF) results in a high patient and societal burden. Telemedicine has been incorporated into multidisciplinary integrated care programs, allowing closer patient monitoring at a lower health system burden. The COVID-19 pandemic boosted telemedicine utilisation, namely telephone consultation (TC). We aimed at evaluating TCs' efficacy and safety in HF patients' management during the COVID-19 pandemic. Methods: All consecutive patients attending a Portuguese HF-Clinic from March to August 2020 were included in this observational study. First medical appointment in this period was defined as the index visit. One-year prospective and retrospective data regarding the patients' status, consultations (face-to-face consultations (FFC) and TC) and acute HF events (AHFE) (unplanned visits, emergency room visits and hospitalisations) were collected. Consultations and AHFE occurring during the 12-month follow-up were compared to the previous year. Results: Overall, 364 patients were included. During a 12-month follow-up, 1107 consultations were registered, 695 FFC and 412 TC. TCs were implemented primarily due to COVID-19 constraints (41%) and for stable patients monitoring (37%). The number of consultations increased after the implementation of TC, compared to the previous year (1107 vs 662) (p<0.001). A total of 94 AHFE were registered during the 12-month follow-up. They occurred more frequently after an FFC than a TC (90 vs 19) (p<0.001). The number of AHFE occurring during the 12-month follow-up was similar to the previous year (94 vs 97) (p>0.05). Conclusion: TCs implementation improved HF patients' monitoring during COVID-19 without AHFE increasing, thus showing efficacy and safety in HF management.